Problematika Alokasi Dana Zakat di Baitul Mal wa Tamwil untuk Mengatasi Non Performing Financing - Suryati, Suryati; Rahmayanti, Dini; Suryana, Yana (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This paper emerged with the circulation of news and controversy regarding the cases of BMTs trying to solve the problem of non-performing financing (NPL) by utilizing the distribution of zakat funds. This research aims to analyzing nonperforming loan mambers at BMT who is categorize as a gharimin. This research is a type of descriptive research with qualitative methods. The data analysis technique used inductive technique. Data analysis is used to examine and find views of sharia law regarding the use of zakat funds for financing problem financing for BMT customers. The principle of permissibility or permissible is used as an analytical knife to study and find answers to the formulation of the problem. Based on the results of the analysis, both classical and contemporary fiqh views allow the distribution of zakat funds to cover non-performing financing provided that the customer meets the requirements to be considered as gharimin and does not oppress those who have entrusted their zakat funds to BMT. However, in reality the financing experienced by many BMTs is mostly due to the bad behavior of the customers themselves and poor business management. This is what often causes the unwillingness of people who have entrusted their zakat funds to BMT on the grounds that BMT is not trustworthy in distributing zakat.